PERANAN DESAIN KEMASAN PRODUK CERIPING GEDHANG DALAM MENINGKATKAN MINAT BELI KONSUMEN PT BUMAY KACBAWJAYA - Yolandha Cindy Kafita; Ni Made Ida Pratiwi (Cahaya Ilmu Bangsa, 2024)
Banana is a plant whose fruit is often consumed by the people of Indonesia. There are many types of bananas in Indonesia, such as Ambon bananas, King bananas, Horn bananas, and many other types. Not only processed by frying, Indonesians are also very happy with banana chips. The process of making banana chips is actually not too difficult, but it requires patience, time, and special attention so that the banana chips can be successful. From this, many Indonesians prefer to buy banana chips instead of making their own. Product packaging design is one of the factors in supporting consumer purchasing interest. Product Packaging Design must also be carefully thought out by entrepreneurs because it contains important elements in attract consumers' attention and influence their purchasing decisions such as product information, functionality, visual appeal, and message clarity.